Amino Acid Structure Determines the Immune Responses Generated by Peptide–Gold Nanoparticle Hybrids. (16th July 2013) - Yang, Hong; Zhou, Yingzhe; Fung, Shan‐Yu; Wu, Licun; Tsai, Kevin; Tan, Rusung; Turvey, Stuart E.; Machuca, Tiago; de Perrot, Marc; Waddell, Thomas K.; Liu, Mingyao
<x xml:space="preserve">Abstract</x> By tuning the chemical modalities on gold nanoparticle surface using hexapeptide ligands the responses of immune cells (dendritic cells) to nanoparticles can be remarkably manipulated from minimum reaction (in the presence of negatively charged peptide ligands) to activation (in the presence of peptide ligands with aromatic rings containing amino acids). <boxed-text content-type="graphic" position="anchor" orientation="portrait"> </boxed-text>